2022
DOI: 10.1155/2022/6449607
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation of PCL Electrospun Fibers Loaded with Cisplatin and Their Potential Application for the Treatment of Prostate Cancer

Abstract: Prostate cancer is a global fatal type of cancer. It is a type of cancer that affect men. Signs and symptoms of the disease include blood in the urine, pain when one micturates, and difficulties in penis erection. Cisplatin chemotherapy is a principal treatment normally given to the prostate cancer patients. Nonetheless, on its own, cisplatin loses efficacy once administered due to liver pass effects and other biochemical attacks. In this paper, we looked at preparation of PCL nanoparticles loaded with cisplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…[57][58][59] These properties have been shown to be intimately related to the diameter, morphology and uniformity of produced nanofibers. 60 Table 1 summarizes the these factors in the electrospinning process and the corresponding affected nanofiber properties. 61 Beyond singleconstituent polymers, polymer blends have been utilized, as well as nanoparticle (NP)-impregnated or drug/ligandimpregnated polymers.…”
Section: Principles and Methodsmentioning
confidence: 99%
“…[57][58][59] These properties have been shown to be intimately related to the diameter, morphology and uniformity of produced nanofibers. 60 Table 1 summarizes the these factors in the electrospinning process and the corresponding affected nanofiber properties. 61 Beyond singleconstituent polymers, polymer blends have been utilized, as well as nanoparticle (NP)-impregnated or drug/ligandimpregnated polymers.…”
Section: Principles and Methodsmentioning
confidence: 99%
“…Over the past decades, remarkable advances have occurred in nanotechnology, particularly nanomedicine, focusing, among others, on novel cancer therapeutics [ 35 ]. NPs can accumulate in cells without being recognized by p -glycoproteins, one of the primary mediators of multidrug resistance, resulting in increased intracellular concentrations of drugs [ 36 ]. Notably, NP carriers exhibit intrinsic abilities affecting cancer and immune cell biological functions [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%